The Transcription Factor c-Maf Promotes the Differentiation of Follicular Helper T Cells - Andris, Fabienne; Denanglaire, Sébastien; Anciaux, Maelle; Hercor, Mélanie; Hussein, Hind; Leo, Oberdan (Frontiers in Immunology, 2017)
Follicular helper T cells (Tfh) have been identified as the primary cell subpopulation regulating B cell responses in germinal centers, thus supporting high affinity antibody production. Among the transcription factors orchestrating Tfh cell differentiation and function, the role played by the proto-oncogene c-Maf remains poorly characterized. We report herein that selective loss of c-Maf expression in the T cell compartment results in defective development of Tfh cells in response to both antigen/adjuvant vaccinations and commensal intestinal bacteria. Accordingly, c-Maf expression in T cells was essential for the development and high affinity antibody secretion in vaccinated animals. C-Maf was expressed early, concomitantly to BCL6, in Tfh cell precursors and found to regulate Tfh fate in a cell-autonomous fashion. Altogether, our findings reveal a novel, non-redundant, function for c-Maf in the differentiation of Tfh cells and the regulation of humoral immune responses to T-cell dependent antigens.